Failure of the corporate responsibility system in a large multinational corporation case study "Dieselgate" - Blažek, Ladislav; Vlastimil, Slovák (Univerzita Pardubice, 2018)
Corporate Social Responsibility (CSR) is an important factor of the positive image of corporations and their competitiveness. However, in some cases, serious misconduct occurs in this area. The article summarizes the results of qualitative research into the failure of the Volkswagen Group’s corporate social responsibility system. The purpose of this research, conducted in the form of a case study, was to elucidate the causes and consequences of fraudulent behavior of falsifying the results of exhaust emission tests for diesel-powered cars. It was found that the main cause was the Group’s organizational culture characterized by very strong elements of competition where the strategic goal had to be met at any cost. If necessary, it would include ways that are contrary to the ethical code. The whole sophisticated CSR system of the Volkswagen Group fatally failed in this case. The consequences became evident mainly in a significant reduction in the market value of the Group and a decrease in investors’ confidence. It is clear that the experience of this case goes significantly beyond the limits of the Volkswagen Group. It can be assumed that it will significantly affect the behavior of companies not only in the automotive industry, but also in other sectors. Further to this case, the critique of the current CSR concept is also becoming more intense and the first impulses to redesign this concept have started to occur.
Keywords: corporate social responsibility; case study; sustainability report; code of conduct; Volkswagen group; Dieselgate; L62; M14